Use of a complete autologous blood recovery system (the Sorin Xtra® Autotransfusion System) during mechanical thrombectomy of extensive cerebral venous sinus thrombosis. Issue 5 (October 2017) - Castaño, C; Cubells, C; Remollo, S; García-Sort, MR; Terceño, M
Background: The endovascular therapy for cerebral venous sinus thrombosis (CVST) is currently accepted as a second-line treatment for patients who have failed or those in whom systemic anticoagulation is contraindicated or in a subgroup of patients presenting with rapid neurologic deterioration. A number of different mechanical and pharmacologic endovascular strategies have been reported, either as separate or combined approaches. These new catheters and aspiration systems have a high power and vacuum capacity, which carries a risk of anemization of the patient and hypovolemic shock, being necessitating the transfusion of the patient. Material and methods: Because of the problems that donor blood transfusion can bring, we describe the use of a Sorin Xtra® Autotransfusion System (ATS). This complete autologous blood recovery system was designed for use in procedures where medium- to high-volume blood loss occurs, such as major surgeries. We have adapted it to recover all the blood aspirated during the mechanical thrombectomy procedures of the dural cerebral venous sinuses, since they are procedures that can cause a significant loss of blood. One advantage to this is the patient receives his or her own blood instead of donor blood, so there is no risk of contracting outside diseases or transfusion reactions. Conclusions: This technical note describes a novel and previously unpublished technical approach to CVST that can be immediately applied to clinical practice. It also raises awareness among the interventional neuroradiologist and anesthesiologist communities about novel, potentially lifesaving endovascular treatments in patients with extensive CVST.